JUSTICE AND LEGAL SETTING ASIDE OF MARITAL PROPERTY: FULFILLMENT OF SUBSTANTIVE JUSTICE IN THE SETTLEMENT OF MARITAL PROPERTY DISPUTES THROUGH A PEACE AGREEMENT (AS-SULHU) - Yusman, Muhammad; Al Amruzi, M. Fahmi; Wahidah, Wahidah (Proceeding International Seminar of Islamic Studies, 2024)
This paper discusses efforts to fulfill substantive justice by setting aside the applicable marital property law. The focus of the research lies on the practice of resolving disputes over the division of marital property by related parties (spouses or ex-spouses, and judges) who set aside the applicable marital property law through a peace agreement (As-Sulhu). This research has important significance because it raises issues that are quite sensitive in society, especially couples or ex-husbands and wives who experience disputes related to marital property. Optimizing dispute resolution through As-Sulhu is a step by judges in realizing substantive justice when deciding marital property disputes. The socio-legal legal research method is applied by deeply analyzing legal materials and explaining the legal context. Empirical data needed for a holistic picture is obtained through observation, interviews, and other methods according to research needs. Qualitative analysis with theoretical and juridical interpretation techniques was used. The results showed that the applicable regulations related to the division of marital property have not met the criteria of substantive justice. Therefore, the practice involves related parties (spouses or ex-spouses and judges) resolving marital property disputes by overriding existing legal provisions, seeking alternatives through As-Sulhu, and strengthening them with court decisions.